Pemetaan Pola Antara Kepemilikan Tripartit, Karakteristik Dewan, dan Debt Structure Yang Membentuk Financial Distress - Desi Argita Karismawati; Erma Setiawati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2026)
This research aims to analyze the influence of Tripartite Ownership (Managerial, Institutional, and Government Ownership), Board Characteristics (Board Size), and Debt Structure on Financial Distress in Basic Materials sector companies listed on the Indonesia Stock Exchange during the 2022-2024 period. The method utilized is quantitative with multiple linear regression analysis techniques. The research population includes all Basic Materials sector companies listed on the IDX, with 86 companies selected as samples using purposive sampling, resulting in 258 observations throughout the research period. The outcomes reveal that managerial ownership, government ownership, board size, and debt structure have a negative and significant effect on financial distress, while institutional ownership has no significant effect.